Feasibility and acceptability of adherence support for direct acting antiviral therapy for hepatitis C in a low‐threshold primary health‐care opioid agonist treatment program. (13th February 2019) - Chronister, Karen J.; Lothian, Rebecca; Gilliver, Rosie; Kearley, John; Read, Phillip
Abstract: Introduction and Aims: To maximise the benefits of direct acting antivirals in Australia, innovative options for marginalised populations to receive daily or weekly medication may be beneficial. This study evaluated the feasibility and acceptability of direct acting antivirals provision by leveraging an opioid agonist treatment program to support adherence regardless of opioid agonist treatment enrolment. Design and Methods: Feasibility was evaluated by monitoring selection of dosing options by clients initiating direct acting antivirals during the first 6 months. Client acceptability was assessed using a cross‐sectional survey after 6 months. Pre‐ and post‐implementation surveys of attitudes and concerns regarding the program were compared to evaluate staff acceptability. Results: Among 79 clients commencing direct acting antivirals, 30 (38%) chose adherence support. Among these, 12 (40%) were not simultaneously enrolled in opioid agonist treatment. Clients were satisfied with service provision and access despite introducing daily dosing. All highly marginalised clients receiving direct acting antivirals with adherence support found this helpful. Staff concerns identified prior to the program proved unfounded. Discussion and Conclusions: This study demonstrates providing adherence support for direct acting antivirals regardless of client participation in opioid agonist treatment is both feasible and acceptable with minimal impact on service provision. Availability of direct acting antivirals in opioid agonist treatment or primary health‐care settings expands the pool of people who may receive effective treatment for hepatitis C virus and reduces treatment barriers.